Additive Effects of Omega-3 Fatty Acids and Thiazolidinediones in Mice Fed a High-Fat Diet: Triacylglycerol/Fatty Acid Cycling in Adipose Tissue - Bardova, Kristina; Funda, Jiri; Pohl, Radek; Cajka, Tomas; Hensler, Michal; Kuda, Ondrej; Janovska, Petra; Adamcova, Katerina; Irodenko, Ilaria; Lenkova, Lucie; Zouhar, Petr; Horakova, Olga; et al. (Nutrients, 2020)
Long-chain n-3 polyunsaturated fatty acids (Omega-3) and anti-diabetic drugs thiazolidinediones (TZDs) exhibit additive effects in counteraction of dietary obesity and associated metabolic dysfunctions in mice. The underlying mechanisms need to be clarified. Here, we aimed to learn whether the futile cycle based on the hydrolysis of triacylglycerol and re-esterification of fatty acids (TAG/FA cycling) in white adipose tissue (WAT) could be involved. We compared Omega-3 (30 mg/g diet) and two different TZDs-pioglitazone (50 mg/g diet) and a second-generation TZD, MSDC-0602K (330 mg/g diet)-regarding their effects in C57BL/6N mice fed an obesogenic high-fat (HF) diet for 8 weeks. The diet was supplemented or not by the tested compound alone or with the two TZDs combined individually with Omega-3. Activity of TAG/FA cycle in WAT was suppressed by the obesogenic HF diet. Additive effects in partial rescue of TAG/FA cycling in WAT were observed with both combined interventions, with a stronger effect of Omega-3 and MSDC-0602K. Our results (i) supported the role of TAG/FA cycling in WAT in the beneficial additive effects of Omega-3 and TZDs on metabolism of diet-induced obese mice, and (ii) showed differential modulation of WAT gene expression and metabolism by the two TZDs, depending also on Omega-3.
Keywords: myši obézní; Male; obesity; Obesity; Fatty Acids, Omega-3; mastné kyseliny; Mice, Obese; obezita; thiazolidindiony; omega-3 mastné kyseliny; Adipocytes; Diet, High-Fat; mužské pohlaví; dieta s vysokým obsahem tuků; Fatty Acids; adipocytes; metabolismus lipidů; triglyceridy; Pioglitazone; bílá tuková tkáň; Adipose Tissue, White; glucose homeostasis; lipogenesis; tukové buňky; Thiazolidinediones; hypoglykemika; Animals; pioglitazon; insulin; zvířata; Lipid Metabolism; myši inbrední C57BL; myši; Hypoglycemic Agents; Mice, Inbred C57BL; Mice; lipogeneze; Lipogenesis; Triglycerides